The AGE of Biomaterials: Preserving the Myocardium after Infarction to Promote Heart Repair and Function - Blackburn, Nicholas (Université d'Ottawa / University of Ottawa, 2017)
Myocardial infarction (MI) persists as one of the leading causes of death worldwide. Often patients whom survive the initial injury will develop heart failure characterized by a dilated and functionally incompetent heart. Heart failure (HF) carries a worse prognosis than most cancers, and the only curative therapy to date is heart transplantation. A better understanding of the repair and remodeling processes post-MI, and the development of novel therapies are required to combat this burgeoning medical challenge. This thesis research sought to identify a novel mediator of the impaired cardiac remodeling that often occurs post-MI, and to characterize a biomaterial hydrogel therapy as a novel treatment. We investigated the role of methylglyoxal (MG), an important precursor to advanced glycation end-products (AGE), using a transgenic mouse model to over-express glyoxalase 1 (GLO1). GLO1 is the primary enzyme involved in metabolizing MG and preventing its accumulation. The role for MG and AGEs in MI and HF had been alluded to in the literature, yet no study to date has causally linked them with the loss of function and impaired remodeling of the post-MI heart. We also assessed an injectable hydrogel for the treatment of MI using a mouse model and evaluated the impact of delivery timing on its therapeutic efficacy. In this thesis, we confirmed that MG derived AGEs accumulate post-MI (Chapter 3.1). We show that preventing their accumulation, through GLO1 over-expression, mitigates the loss of function post-MI and positively influences remodeling through reducing final infarct sizes and end-systolic volumes. We demonstrate that this may possibly occur through improving the bone marrow response post-MI by restoring ECM-cell signaling. In Chapter 3.2, we present results of a study assessing the efficacy of a collagen based injectable hydrogel for the treatment of MI, and assessing the role that timing plays into the benefits associated with this therapy by studying 3 separate timepoints including 3 hours, 7 days and 14 days post-MI. We found that the injectable hydrogel preserved cardiac function and reduced infarct sizes. It also positively interacted with the host repair response by reducing chronic inflammation and cell death. The benefits of the therapy depended on when the material was delivered, and we found that the earliest timepoint (3 hours post-MI) proved most beneficial. In Chapter 3.3, we combined the knowledge gained from Chapters 3.1 and 3.2 and functionalized our hydrogel with a flavonoid, Fisetin, that has been shown to scavenge MG and increase the activity of GLO1. We show that this novel functionalized material may be able to restore some function in MI, particularly in settings of low baseline cardiac function. Taken together, the results of this thesis demonstrate that MG accumulates as a result of the ischemia and contributes to the impaired repair resolution and remodeling processes post-MI. This identifies MG as a possible novel target for the treatment of MI. Indeed, we also confirm the role that delivery timing plays into injectable hydrogels post-MI, and present promising results for a functionalized material design to intervene on MG production.
Keywords: Myocardial Infarction; Molecular Medicine; Biomaterials; GLO1; Methylglyoxal; Advanced Glycation End-Products